Government Action on Violence Against Women: Enhancing Good Governance in Regional Units: Tindakan Pemerintah Terhadap Kekerasan Terhadap Perempuan: Meningkatkan Tata Pemerintahan Daerah - Rodiyah, Isnaini; Nisa, Arum Choirun (Indonesian Journal of Public Policy Review, 2023)
This qualitative descriptive research explores the government's performance in handling women's violence with a focus on UPTD PPA, aiming to achieve good governance. Data were gathered through observation, interviews, documentation, and literature study, employing purposive sampling. Findings reveal that UPTD PPA falls short in realizing good governance, with deficiencies in accountability, transparency, and community participation indicators. Supporting factors include government regulations and budgetary support, along with collaboration from various agencies. Inhibiting factors involve divergent views on violence handling between UPTD PPA and the police, coupled with low public trust. This study underscores the need for enhanced collaboration and public engagement to strengthen the government's response to women's violence. Highlight : Challenges in Accountability: Lack of transparency and accountability in budget utilization by UPTD PPA hinders the realization of good governance in addressing women's violence. Technology Deficiency: Absence of technological tools for information dissemination impairs transparency within UPTD PPA, posing a barrier to effective communication with the public. Interagency Collaboration and Public Trust: Successful collaboration with government entities like the police, prosecutors, hospitals, and social services supports effective handling of women's violence, while addressing differences in understanding between UPTD PPA and the police is crucial for overall success. Keywords: Government Performance, Women's Violence, Good Governance, UPTD PPA, Collaboration